Secular trends of use of anti-osteoporosis treatments in Spain: a population-based cohort study including over 1.5 million people and more than 12 years of follow-up - Martín-Merino, E; Huerta-Álvarez, C; Prieto-Alhambra, D; Álvarez-Gutiérrez, A; Montero-Corominas, C (Elsevier, 2017)
Objective Different regulatory actions for anti-osteoporosis medication (AOM) were taken during the last years, including marketing of new drugs, safety warnings, or restrictions on the indications. We aimed to characterise the secular trends of AOM use in Spain from 2001 to 2013. Methods A cohort study using the Spanish Database for Pharmacoepidemiological Research in Primary Care (BIFAP), was performed. BIFAP includes anonym records for 4 million patients. Participants entered the study when aged ≥50 years in 2001-2013 and after 1 year of data available, and were followed to an AOM prescription (including alendronate, other bisphosphonates, SERM (selective estrogen receptor modulators), strontium ranelate, teriparatide or denosumab), death, lost or the end of December 2013. Prevalence (%) and incidence rate (IR/1,000 person-years (py)) of AOM users were computed by years and sex. Results Out of 1.5 million participants, 135,410 received AOM treatment during 2001-2013. Prevalence was 6.1% (women) and 1.1% (men),that increased from 2001 (2.0%) to 2009 (7.6%) to decrease thereafter. Out of them, 95,057 were incident. The IR was 24.9 (women) and 2.8 (men), that increased from 2001 (21.25 and 1.96) to 2007 (35.84 and 3.64), and decreased to 12.48 and 1.81 (2013). IRs were highest for bisphosphonates along the years (ranging 3.70-14.73 and 0.57-1.75 in women and men respectively), followed by SERM up to 2005 (6.51-9.02 and 0.06-0.07), and strontium ranelate from 2006 (4.66 and 0.45) to 2012 (2.05 and 0.26). IR for teriparatide increased from marketing in 2004 (0.10-1.01 and 0.02-0.29), as was denosumab from marketing in 2011 (0.03-2.64 and 0.09-0.15). Conclusions Population-based estimates of AOM use in Spain peaked in 2007-2009 and decreased thereafter, irrespective of age and sex. New treatments were ten times higher in women than men. Bisphosphonates were the most frequently prescribed class, followed by SERM in women before 2006, strontium otherwise till 2012, and denosumab in women or teriparatide in men in 2013. Changes in the osteoporosis criteria, fracture risk assessment strategies, and regulatory actions for AOM around the time, may explain that trend.